Body-parts and possessive constructions in Mataguayan languages - Nercesian, Verónica (2022)
This paper argues for the existence of an early possessive classifier *t(V)- that may have distinguished body-parts from the rest of the inalienable nouns in the Mataguayan language family. Evidence of this is the documentation of a t(V)-form or a t(V)-form series in the possessive flexional paradigms in this family. In most cases, it is synchronically reanalysed as a possessive prefix fused to the pronominal possessive prefixes, while in others, *t(V)- seems to have been fused to the root. This suggests that, in Proto-Mataguayan, there may have been only one pronominal series indexing possessor, and that *t(V)- was related to the meaning of the root. We also posit there is a relationship with a formally similar verbal prefix, which classifies agentive intransitive roots, and a presumable semantic extension of *t(V)- from body-part nouns to agency in intransitive predicates.